MANAJEMEN SUMBER DAYA MANUSIA PADA IKATAN MUBALLIGH SULAWESI TENGGARA (IMSULTRA) - Syamsuddin Syamsuddin (Institut Agama Islam Negeri Kendari, 2019)
This study aims to analyze the implementation of the da’wah management conducted by IMSULTRA. This research is a descriptive qualitative type conducted in Southeast Sulawesi. The results of this study indicate that the management of the da’wah implemented by the DPW IMSULTRA has not been done comprehensively. This can be seen from the process of planning, recruiting, organizing, monitoring, and evaluating the muballigh which have not done in a comprehensive and systematic way. The alternative solution that can be done by DPW IMSULTRA to overcome the obstacles faced or at least minimize the negative implications caused is to recruit several personnel (staff) whose duty is to carry out various technical matters, form a more specific and comprehensive work program every year, compile analysis the needs of the muballigh, selective recruitment, compile job descriptions for each clear element to improve the lecture scheduling system, and implement a better muballigh monitoring and evaluation system.